Preterm birth: Case definition & guidelines for data collection, analysis, and presentation of immunisation safety data - Quinn, Julie-Anne; Munoz, Flor M.; Gonik, Bernard; Frau, Lourdes; Cutland, Clare; Mallett-Moore, Tamala; Kissou, Aimee; Wittke, Frederick; Das, Manoj; Nunes, Tony; Pye, Savia; Watson, Wendy; et al. (Vaccine, 2016)
Preterm birth is commonly defined as any birth before 37 weeks completed weeks of gestation. An estimated 15 million infants are born preterm globally, disproportionately affecting low and middle income countries (LMIC). It contributes directly to estimated one million neonatal deaths annually and is a significant contributor to childhood morbidity. However, in many clinical settings, the information available to calculate completed weeks of gestation varies widely. Accurate dating of the last menstrual period (LMP), as well as access to clinical and ultrasonographic evaluation are important components of gestational age assessment antenatally. This case definition assign levels of confidence to categorisation of births as preterm, utilising assessment modalities which may be available across different settings. These are designed to enable systematic safety evaluation of vaccine clinical trials and post-implementation programmes of immunisations in pregnancy.